Development and Optimization of Micro‐Nanotopographical Platforms for Surface Enhanced Raman Scattering Biomolecular Detection - David Femi Odetade; Jonathan J. S. Rickard; Pola Goldberg Oppenheimer (Advanced Materials Interfaces)
Abstract Topologically designed micro‐ and nanostructured surface‐enhanced Raman scattering (SERS) substrates propel the advancements of innovative applications, including environmental and forensic point‐of‐care miniaturised devices via enhancing the localised electric fields for accurate analyte sensing. Herein, a method for designing, optimising and fabricating fine‐tuneable concentric hexagonal, triangular and rectangular SERS‐active micronano‐substrates is developed, with each unit yielding significant enhancement. Numerical simulations of the 3D near‐field electric field guided the optimal design process. While the coaxial SERS substrates consistently outperformed their solid counterparts, the hexagonal micro‐nano topologies exhibited ×21 higher signal than coaxial square arrays and a 12‐15‐fold increase over the triangle structures. Alternation of the topological designs from square to triangle lattice yielded more uniform plasmonic modes propagating along the 60°‐directions with various resonance modes playing key roles in light reflectance. This enables the engineering of platforms with tailor‐enhanced signals by changing the arrangement of micro‐nano patterned coaxial arrays. The fabricated SERS substrates are validated by detecting traumatic brain injury biomarkers, effectively yielding the characteristic fingerprint spectra of each neuro‐molecule. The straightforward development of sub‐micrometre tuneable SERS‐active architectures enables anelegant route for high‐throughput biochemical sensing, laying a platform for amplified bimolecular detection of disease biomarkers and integration in bioanalytical systems.